Caries Management№ 4, - Guzman-Armstrong, S. Sandra; Fonrana, M. Margherita; Nascimento, M. M. Marcelle M.; Zandona, A. G.F. Andrea G. Ferreira (Elsevier, 2019)
This issue of Dental Clinics of North America focuses on Caries Management and is edited by Drs. Sandra Guzmán-Armstrong, Margherita Fontana, Marcelle Matos Nascimento and Andrea G. Ferreira Zandona. Articles will include: Non-Surgical management of cavitated and non-cavitated lesions; Approaches to modulate biofilm ecology; Dietary implications in dental caries: A practical approach on nutritional counseling; Motivational communication in the dental practice: On the road to preventing oral disease; Personalized dental caries management in adults; Personalized dental caries management in geriatric and special needs populations; Clinical decision making in the management of dental caries; Surgical management of caries lesions: Selective removal of carious tissues; The interprofessional role in dental caries management: Perspectives from a nurse, physician, and social worker; Third party perspective of dental caries management; Less is more? The long-term health and cost consequences emanating from minimal invasive caries management; Performance of adhesives and restorative materials after selective removal of carious lesions: Restorative materials with anti-caries properties; Personalized dental caries management in children.